(untitled) (Aintelia Science Notes, 2026)
In this study, the design optimization of ventilation components integrated into the interior trim system of 15 m³ panel vans and minibus are investigated. During the analysis process, computer-aided engineering (CAE) methods were employed, and the effects of different design parameters on airflow performance were numerically examined. In order to improve in-cabin air circulation, ventilation duct diameters and vent geometries were evaluated. Accordingly, duct diameters were defined as 50 mm and 70 mm, while vent geometries were modeled as circular and rectangular cross-sections. The results of the flow analyses indicated that the design with a 70 mm duct diameter and a circular vent with a diameter of 68 mm provided the best performance in terms of airflow distribution, pressure loss, and flow uniformity. The findings demonstrate the direct impact of geometric parameters in interior trim design on air quality and passenger comfort. The optimized design approach offers significant contributions in terms of more efficient ventilation, improved passenger comfort, and potential energy savings in service vehicles. It is expected that this study will guide future optimization efforts and interior trim design processes in commercial vehicles.